Management of Carotid Artery Injury in Endonasal Surgery - Padhye, Vikram; Valentine, Rowan; Wormald, Peter-John (International Archives of Otorhinolaryngology, 2014)
Introduction Carotid artery injury (CAI) is the most feared and potentially catastrophic intraoperative complication an endoscopic skull base surgeon may face. With the advancement of transnasal endoscopic surgery and the willingness to tackle more diverse pathology, evidence-based management of this life-threatening complication is paramount for patient safety and surgeon confidence.Objectives We review the current English literature surrounding the management of CAI during endoscopic transnasal surgery.Data Synthesis The searched databases included PubMed, MEDLINE, Cochrane database, LILACS, and BIREME. Keywords included “sinus surgery,” “carotid injury,” “endoscopic skull base surgery,” “hemostasis,” “transsphenoidal” and “pseudoaneurysm.”Conclusions Review of the literature found the incidence of CAI in endonasal skull base surgery to be as high as 9% in some surgeries. Furthermore, current treatment recommendations can result in damage to critical neurovascular structures. Management decisions must be made in the preoperative, operative, and postoperative setting to ensure adequate treatment of CAI and the prevention of its complications such as pseudoaneurysm. Emphasis should be placed on surgical competency, teamwork, and technical expertise through education and training.
Keywords: carotid injury; hemorrhage; sinus surgery; endoscopic skull base surgery